2010
DOI: 10.1177/039463201002300141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anti-Bacterial Prophylactic Properties of Two Different Vascular Grafts: Action of Anti-Bacterial Graft Coating and Systemic Antibiotic Treatment

Abstract: M.A. and G.L.S. contributed equally to this researchThe main problem associated with artificial vascular devices is the risk of bacterial infections, mostly sustained by coagulase negative staphylococci or Staphylococcus aureus. Many efforts have been made to identify materials refractory to bacterial adhesion. The aim of our study is to verify the antimicrobial properties of two kinds of vascular prosthesis to prevent early onset infections and the efficacy of the concomitant action of a systemic antibiotic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Different results were obtained. In the study of Artini et al (24), IGS could prevent infection at 21 days if a low bacterial load (10 5 CFU/ml) was used, but not when a high bacterial load was applied (10 8 CFU/ml). This effect disappeared when no systemic antibiotics (levofloxacin intraperitoneally for seven days) were given.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Different results were obtained. In the study of Artini et al (24), IGS could prevent infection at 21 days if a low bacterial load (10 5 CFU/ml) was used, but not when a high bacterial load was applied (10 8 CFU/ml). This effect disappeared when no systemic antibiotics (levofloxacin intraperitoneally for seven days) were given.…”
Section: Resultsmentioning
confidence: 98%
“…Seven articles studied a commercially available silver coated graft in an animal model. (8,15,17,(24)(25)(26)(27) In this group, two studies added rifampicin soaking onto the silver coated graft. This combination resulted in an augmented antibacterial activity and a prolonged release of antibiotic and silver in the perigraft site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the use of antibiotic-bound grafts or systemic antibiotic treatment alone cannot prevent PVGI. 9,19,25 Furthermore, the systemic administration of rifampicin and ciprofloxacin in combination can avert the development of rifampicin resistance and achieve a higher cure rate. 26,27 In the present study, the bacteria spread into the perigraft and the aortic tissues 14 days after inoculation, and the infected tissues were not completely cleared even after performing intensive debridement.…”
Section: Discussionmentioning
confidence: 99%
“…In physiological conditions, humans can hold 8-9 litres of liquid in the intestinal tract, and only about 10% of this is reabsorbed. Enteric E. coli can alter this balance, causing strong discharges of diarrhoea (26)(27)(28)(29). Enteric attacks are better controlled if the infection is controlled.…”
mentioning
confidence: 99%